Implementation of Wakelet-Based “Smart-Hub Media” to Enhance Critical Thinking and Self-Regulated Learning Among Students - Alya Salsabila Setyawan; Madziatul Churiyah; Ardian Novianti (Transpublika Publisher, 2026)
In the era of digital educational transformation, the integration of innovative learning technologies plays a crucial role in shaping autonomous and high-order thinking skills among vocational school students. This research is motivated by the low critical thinking skills and self-regulated learning of tenth-grade MPLB 1 students at SMK Negeri 1 Kota Malang, due to the issue of using conventional and passive learning media. This research aims to implement Wakelet-based ‘Smart-Hub Media’ as an integrated digital ecosystem to improve both aspects. The method used is Classroom Action Research (CAR) based on Kurt Lewin’s model, conducted across two cycles with a subject pool of 30 students. Data on critical thinking were gathered via pre-test and post-test designs and subsequently analyzed using an Independent Samples T-Test, while self-regulated learning data were assessed using a percentage-based questionnaire. The results of the study showed a significant increase in students’ critical thinking skills, with the class average score soaring from 49.1 (initial) to 93.4 at the end of cycle II, successfully exceeding the Minimum Completion Criteria (KKM) with t (count) > t (table) at a significance level of 0.05. Concurrently, the self-regulated learning questionnaire yielded an average score of 84%, falling into the ‘Very High’ category. It is concluded that the implementation of Wakelet-based ‘Smart-Hub Media’ is effective and feasible for enhancing students’ critical thinking and self-regulated learning.